Bukti Empiris Nilai Ekonomik Pada Pengumuman Daftar Efek Syariah (DES) Di Indonesia - Syafiq M. Hanafi (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2013)
This article attempt to study about the impact of Islamic ethical investment in Indonesia. The method of this research by event study of the announcement of the list of syariah stock. I argue the announcement of stock has economic value by signalling hypothesis, criteria selection hypotesis andprice pressure hypothesis. The research finding show that the information of announcement of the list of syariah stock has economic value by positive reaction at the day.